STRATEGI KEPEMIMPINAN KEPALA MADRASAH DALAM MEMANFAATKAN ICT GUNA MENINGKATKAN MUTU PENDIDIKAN DI MIM KRAGILAN SIMO BOYOLALI - Wahyudi, Widodo Tri; Supriyanto, Supriyanto; Rifa’i, Andi Arif (FIKRAH, 2024)
The aim of this research is to find out the leadership strategy of madrasah heads in utilizing ICT to improve the quality of education at Mim Kragilan Simo Boyolali. Because, the quality of education results from the learning process, in learning it requires planning and implementation as well as evaluation of various elements of education, no less important is the role of a madrasa head. This research uses qualitative research methods with a descriptive approach. This means procedures or ways of solving research problems by describing the object under study as actual facts that are occurring/taking place at the present time. The subject of this research was the head of the MIM Kragilan Boyolali madrasah, while the informants included the school principal, teachers and students. Data collection methods in this research are observation methods or non-participant observation, interview methods and documentation methods. The data analysis process begins by reviewing all data from interviews, observations and comments related to the use of ICT to improve the quality of education, followed by data reduction and verification to draw conclusions. The results of this research are: (1). The Madrasah Head encourages and directs teachers and students to follow the use of social media. (2) The Madrasah Head always provides a good example to his students and teachers. (3) The Madrasah Head always tries enthusiastically to improve the learning process and learning output by utilizing ICT.